Effect of Rainfall Characteristics on The Stability of Tropical Residual Soil Slopes - Elsa Nafriza; Herwan Dermawan; Mardiani Mardiani (Politeknik Negeri Lhokseumawe, 2025)
This study investigated a slope with tropical residual soil, utilizing SEEP/W and SLOPE/W modules within the Geostudio finite element analysis software. The research focused on examining changes in slope stability under various rainfall patterns and soil parameters. Subsequently, curves illustrating the variation of slope’s factor of safety over rainfall duration were obtained. The result indicate that the advance rainfall pattern has a more significant impact on slope stability compared to the delayed, uniform and peak patterns. Under different rainfall pattern, continuous rain consistently leads to gradual decrease in slope stability. An increase in rainfall directly causes a rise in pore water pressure and a reduction in the factor of safety. Steeper slopes exhibit a more extreme decrease in the factor of safety. The advanced pattern result in a rapid pore water pressure response and a drastic drop in the factor of safety in a short time.